Fabrication and investigation of high-quality glass-ceramic (GC)–polymethyl methacrylate (PMMA) composite for regenerative medicine. Issue 53 (3rd July 2017) - Golubevas, Ricardas; Zarkov, Aleksej; Alinauskas, Laurynas; Stankeviciute, Zivile; Balciunas, Giedrius; Garskaite, Edita; Kareiva, Aivaras
Abstract : Investigations of mechanical and dissolution properties show glass ceramic–PMMA composite potential for regenerative medicine when extreme strength is not required. Abstract : The preparation of a glass-ceramic (GC)–polymethyl methacrylate (PMMA) composite material is reported. Precursor GC powders were synthesised via sol–gel method at 600 °C. XRD analysis revealed the formation of sodium calcium silicate (Na6 Ca3 Si6 O18 ) as a main constituent phase of GC powders. The cylindrical-shaped GC–PMMA composite samples with fractional GC content ranging from 75 to 95% were prepared via photopolymerization reaction. The largest compressive strength for the composites containing 90% of GC has been determined. The growth of ceramic layer on the surface of composites immersed into simulated body fluid (SBF) under static conditions was studied by ICP-OES, FE-SEM/EDX, FTIR and XRD techniques. The changes in the concentrations of Ca, Si and P after the dissolution indicate the degradation process of GC–PMMA composites. The structures of the resultant surface confirmed the formation of new ceramic layer on the surface of composite materials. FTIR and XRD analyses revealed the deposition of low-crystallinity calcium phosphate layer with the composition similar to that of the carbonated hydroxyapatite (cHAP) after the soaking in SBF.